Field notes contributed by Thomas H. Kent with verifying documentation, summer 1981 - Kent, Thomas H. (Thomas Hugh), 1934-et al (1981)
Summer report of birds contributed by Thomas H. Kent. Verifying documentation of extraordinary sightings of Say's Phoebe and Western Grebe are included. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1981. Epson - sheet feed